Stabilization of an Enantiopure Sub‐monolayer of Helicene Radical Cations on a Au(111) Surface through Noncovalent Interactions. Issue 28 (8th June 2021) - Giaconi, Niccolò; Sorrentino, Andrea Luigi; Poggini, Lorenzo; Lupi, Michela; Polewczyk, Vincent; Vinai, Giovanni; Torelli, Piero; Magnani, Agnese; Sessoli, Roberta; Menichetti, Stefano; Sorace, Lorenzo; Viglianisi, Caterina; et al.
Abstract: In the past few years, the chirality and magnetism of molecules have received notable interest for the development of novel molecular devices. Chiral helicenes combine both these properties, and thus their nanostructuration is the first step toward developing new multifunctional devices. Here, we present a novel strategy to deposit a sub‐monolayer of enantiopure thia[4]helicene radical cations on a pre‐functionalized Au(111) substrate. This approach results in both the paramagnetic character and the chemical structure of these molecules being maintained at the nanoscale, as demonstrated by in‐house characterizations. Furthermore, synchrotron‐based X‐ray natural circular dichroism confirmed that the handedness of the thia[4]helicene is preserved on the surface. Abstract : A strategy based on noncovalent interactions has been developed to deposit a sub‐monolayer of enantiopure thia[4]helicene radical cations on a pre‐functionalized Au(111) substrate. This approach results in both the paramagnetic character and the chirality of the molecules being retained at the nanoscale.